Gastritis New Approaches and Treatments - Maria Roesler, Bruna (IntechOpen, 2019)
The isolation and identification of Helicobacter pylori as the cause of gastrointestinal diseases had major implications for public health and led to curative treatments that reduced suffering from many acute and chronic conditions. Although alternative therapies have been used to improve eradication, current treatments still rely on a combination of antimicrobial agents often associated with antisecretory agents, such as proton pump inhibitors. In this book there is a comprehensive overview by contributors on H. pylori infection in diverse areas, including a general overview of H. pylori infection, and discussions about the principal therapeutic regimens of bacterium eradication, considering antimicrobial resistance. Also, certain aspects of autoimmune gastritis, an important condition that has been related to microorganism infection, is also considered. H. pylori is clearly a very interesting bacterium and great studies and discussions about all its aspects are welcomed by the medical and scientific communities.